2010
DOI: 10.1088/0004-637x/722/1/248
|View full text |Cite
|
Sign up to set email alerts
|

Local Group Dwarf Spheroidals: Correlated Deviations From the Baryonic Tully-Fisher Relation

Abstract: Local Group dwarf spheroidal satellite galaxies are the faintest extragalactic stellar systems known. We examine recent data for these objects in the plane of the Baryonic Tully-Fisher Relation (BTFR). While some dwarf spheroidals adhere to the BTFR, others deviate substantially. We examine the residuals from the BTFR and find that they are not random. The residuals correlate with luminosity, size, metallicity, ellipticity, and susceptibility of the dwarfs to tidal disruption in the sense that fainter, more el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
178
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(196 citation statements)
references
References 127 publications
(198 reference statements)
16
178
2
Order By: Relevance
“…Ultra-faint dwarf spheroidals are expected to be increasingly affected by this kind of non-equilibrium dynamics, as shown to be true even for Newtonian weak-field dynamics (Kroupa 1997, Sect. 6.1), and even more strongly so in MOND (McGaugh & Wolf 2010).…”
Section: A Consistency Checkmentioning
confidence: 83%
See 1 more Smart Citation
“…Ultra-faint dwarf spheroidals are expected to be increasingly affected by this kind of non-equilibrium dynamics, as shown to be true even for Newtonian weak-field dynamics (Kroupa 1997, Sect. 6.1), and even more strongly so in MOND (McGaugh & Wolf 2010).…”
Section: A Consistency Checkmentioning
confidence: 83%
“…Both the MOND and MOG approaches have been applied to the satellite galaxy problem with appreciable success (Milgrom 1995;Brada & Milgrom 2000;Angus 2008;Moffat & Toth 2008;Hernandez et al 2010;McGaugh & Wolf 2010). It has already been conclusively demonstrated that spiral galaxy rotation curves are well recovered in MOND purely by the baryon distribution without any parameter adjustments (Sanders & McGaugh 2002;McGaugh 2004McGaugh , 2005aSanders & Noordermeer 2007), and MOG is reported to also do well on this account (Brownstein & Moffat 2006).…”
Section: Non-newtonian Weak-field Gravitymentioning
confidence: 99%
“…Many of the uncertainties involved in measuring and interpreting velocity dispersions have been discussed by McGaugh & Wolf (2010). We emphasize here just two possible systematics that we fear will make it extremely difficult to distinguish between the various possibilities.…”
Section: Challenges To Interpretationmentioning
confidence: 96%
“…For example, KK98-251 is a dwarf irregular satellite of NGC 6946, but both lie on the same BTFR with no indication of a shift in normalization. Current data for the ultrafaint dwarf satellites of the Milky Way do place them below the BTFR, but this shift occurs at much smaller scales (V f 20 km s −1 ; Walker et al 2009;Wolf et al 2010;McGaugh & Wolf 2010).…”
Section: Some Specific Modelsmentioning
confidence: 99%